Предмет: Алгебра,
автор: Незнайка1241
ПОМОЩЬ!!!! ПОЖАЛУЙСТА
Приложения:
Ответы
Автор ответа:
0
m^3-n^3 =(m-n)(m²+mn+n²)
m² -n²=(m -n)(m+n)
(m-n)(m²+mn+n²) *(m-n)(m+n) / (m+n)(m²+mn+n²) = (m-n)(m-n) =(m-n)² = m²
-2mn +n²
4) при делении дробь переворачиваем и будет умножение
p² -1 =(p -1)(p +1)
p^3 -q^3=(p-q)(p²+pq+q²)
(p²+pq+q²) *(p -1)(p +1) / (p-1)*(p-q)(p² +pq +q²) = (p+1) /(p-q)
m² -n²=(m -n)(m+n)
(m-n)(m²+mn+n²) *(m-n)(m+n) / (m+n)(m²+mn+n²) = (m-n)(m-n) =(m-n)² = m²
-2mn +n²
4) при делении дробь переворачиваем и будет умножение
p² -1 =(p -1)(p +1)
p^3 -q^3=(p-q)(p²+pq+q²)
(p²+pq+q²) *(p -1)(p +1) / (p-1)*(p-q)(p² +pq +q²) = (p+1) /(p-q)
Похожие вопросы
Предмет: Английский язык,
автор: vilgemina
Предмет: История,
автор: step6ash6ka6
Предмет: Физкультура и спорт,
автор: hotdog335
Предмет: Математика,
автор: nvalker
Предмет: Математика,
автор: наталья0803